RANCANG BANGUN SISTEM INFORMASI E-LEARNING BERBASIS WEB PADA TPQ AL-MAARIJ - Taufik; Silalahi, Mesri (Computer Science and Industrial Engineering, 2022)
E-learning is a teaching and learning process that is assisted by electronic media so that students and teachers can still carry out their activities without having to meet face to face. making e-learning using object-oriented methods. It contains UML methods such as use cases, activity diagrams, sequence diagrams, class diagrams.